Peripheral nerve abnormality in HIV leprosy patients - Xavier, Marilia Brasil (PLoS Negl Trop Dis, 2018)
BACKGROUND: The geographical overlap of HIV (human immunodeficiency virus) and leprosy infection has become increasingly frequent and worrying, bringing many clinical issues. Peripheral neuropathy is very frequent in leprosy because of the predilection of its etiologic agent by Schwann cells of the peripheral nervous system, and it also affects individuals with HIV as one of the most common neurological manifestations. METHODOLOGY/PRINCIPAL FINDINGS: The present study compared a cohort of 63 patients diagnosed with leprosy and coinfected with HIV with a cohort of 64 patients with leprosy alone, who were followed at the outpatient clinic of the Nucleus of Tropical Medicine of the Federal University of Pará, Brazil. We observed that HIV-coinfected leprosy patients presented greater odds of overall peripheral nerve damage (nerve function impairment—NFI) than patients with leprosy alone. More sensitive damage was observed, especially in patients coinfected with multibacillary forms. Leprosy patients coinfected with HIV presented higher chances of motor damage with improvement over time using multidrug therapy (MDT) and highly active antiretroviral therapy (HAART), along with a greater extent of damage and occurrence of neuritis. The data suggest that in addition to patients presenting possible damage caused by leprosy, they also had a greater damage gradient attributable to HIV disease, but not related to HAART because most of these patients had been on the treatment for less than a year. Neuritis was treated with prednisone at doses recommended by the WHO, and coinfected patients had the highest rate of clinical improvement in the first 60 days. CONCLUSIONS/SIGNIFICANCE: The clinical characteristics of the two diseases should be considered in leprosy patients coinfected with HIV for better diagnosis and treatment of peripheral neuropathy. We suggest that new simplified assessment tools that allow the evaluation of the NFI of these patients be developed for use in the service.